Surface patterning of polyacrylamide gel using scanning electrochemical cell microscopy (SECCM). Issue 64 (19th July 2016) - Oseland, Elizabeth E.; Ayres, Zoë J.; Basile, Andrew; Haddleton, David M.; Wilson, Paul; Unwin, Patrick R.
Abstract : Scanning electrochemical cell microscopy is introduced as a new tool for the synthesis and deposition of polymers on SAM-functionalised Au surfaces. Abstract : Scanning electrochemical cell microscopy is introduced as a new tool for the synthesis and deposition of polymers on SAM-functionalised Au surfaces. The deposition of poly( N -hydroxyethyl acrylamide) is shown to be enhanced through the electrochemical generation of activating Cu(i )Cl/Me6 TREN catalyst. Initiation of the polymerisation reaction is most likely due to in situ generation of reactive oxygen species following oxygen reduction.